The Obesity Paradox Predicts the Second Wave of COVID-19 to Be Severe in Western Countries - Krams Indikis A; Jõers Priit; Luoto Severi; Trakimas Giedrius; Lietuvietis Vilnis; Krams Ronalds; Kaminska Irena; Rantala Markus J; Krama Tatjana (MDPI, 2022)
While COVID-19 infection and mortality rates are soaring in Western countries, Southeast Asian countries have successfully avoided the second wave of the SARS-CoV-2 pandemic despite high population density. We provide a biochemical hypothesis for the connection between low COVID-19 incidence, mortality rates, and high visceral adiposity in Southeast Asian populations. The SARS-CoV-2 virus uses angiotensin-converting enzyme 2 (ACE2) as a gateway into the human body. Although the highest expression levels of ACE2 are found in people's visceral adipose tissue in Southeast Asia, this does not necessarily make them vulnerable to COVID-19. Hypothetically, high levels of visceral adiposity cause systemic inflammation, thus decreasing the ACE2 amount on the surface of both visceral adipocytes and alveolar epithelial type 2 cells in the lungs. Extra weight gained during the pandemic is expected to increase visceral adipose tissue in Southeast Asians, further decreasing the ACE2 pool. In contrast, weight gain can increase local inflammation in fat depots in Western people, leading to worse COVID-related outcomes. Because of the biological mechanisms associated with fat accumulation, inflammation, and their differential expression in Southeast Asian and Western populations, the second wave of the pandemic may be more severe in Western countries, while Southeast Asians may benefit from their higher visceral fat depots.